PEDAGOGICAL FOUNDATIONS OF THE IDEAS OF THE JADIDIAN IDEAS - Najmiddinova Saodat Abduvohid qizi (Proximus Journal Publishing, 2024)
This article provides information about the word jadid, the theoretical foundations of jadidism and pedagogical aspects of jadidism, as well as the thoughts and ideas of our scholars who contributed greatly to the idea of jadidism. Also, thoughts and comments about how attention is being paid to the idea of Jadidism in our country today
Keywords: Jadid; educational system; religious education